What are the critical elements of sideline screening that can be used to establish the diagnosis of concussion? A systematic review. Issue 11 (7th March 2017) - Patricios, Jon; Fuller, Gordon Ward; Ellenbogen, Richard; Herring, Stanley; Kutcher, Jeffrey S; Loosemore, Mike; Makdissi, Michael; McCrea, Michael; Putukian, Margot; Schneider, Kathryn J
Abstract : Background: Sideline detection is the first and most significant step in recognising a potential concussion and removing an athlete from harm. This systematic review aims to evaluate the critical elements aiding sideline recognition of potential concussions including screening tools, technologies and integrated assessment protocols. Data sources: Bibliographic databases, grey literature repositories and relevant websites were searched from 1 January 2000 to 30 September 2016. A total of 3562 articles were identified. Study selection: Original research studies evaluating a sideline tool, technology or protocol for sports-related concussion were eligible, of which 27 studies were included. Data extraction: A standardised form was used to record information. The QUADAS-2 and Newcastle-Ottawa tools were used to rate risk of bias. Strength of evidence was assessed using the Grades of Recommendation, Assessment, Development and Evaluation Working Group system. Data synthesis: Studies assessing symptoms, the King-Devick test and multimodal assessments reported high sensitivity and specificity. Evaluations of balance and cognitive tests described lower sensitivity but higher specificity. However, these studies were at high risk of bias and the overall strength of evidence examining sideline screening tools was very low. A strong body of evidence demonstrated that head impact sensors did not provide useful sideline concussion information. Low-strength evidence suggested a multimodal, multitime-based concussion evaluation process incorporating video review was important in the recognition of significant head impact events and delayed onset concussion. Conclusion: In the absence of definitive evidence confirming the diagnostic accuracy of sideline screening tests, consensus-derived multimodal assessment tools, such as the Sports Concussion Assessment Tool, are recommended. Sideline video review may improve recognition and removal from play of athletes who have sustained significant head impact events. Current evidence does not support the use of impact sensor systems for real-time concussion identification.